The Beauty in Art as a Gateway to the Appearance of the Truthfulness of Existence. "On Beauty and Being: Hans-Georg Gadamer’s and Virginia Woolf’s Hermeneutics of the Beautiful", by Małgorzata Hołda, Peter Lang GmbH, Berlin 2021, pp. 310 (rev.) - Hovav Rashelbach (Studia Philosophiae Christianae, 2022)
The book develops the current hermeneutic discourse concerning the notions of beauty and Being. It includes a discussion of melancholic beauty and its interconnection with the act of art’s creation. According to M. Hołda, the writings of both authors demonstrate a treatment of beauty based on ancient Greek thought, especially from the times of Plato and Aristotle. Gadamer reaffirms the intimate relationship between beauty and Being, which is also revealed in Woolf’s literary work.